OIL DECONTAMINATION OF BOTTOM SEDIMENTS EXPERIMENTAL WORK RESULTS - Lushnikov Sergey V.; Frank Yulia A.; Vorobyov Danil S. (Earth Sciences Research Journal)
This article presents the results of experimental work during 2004-2005 on oil decontamination of bottom sediments of Lake Schuchye, situated in the Komi Republic (Northern Russia). The cause of thecontamination were huge oil spills occurred after a series of accidental ruptures on the Harjaga-Usinsk and Vozej-Usinsk oil-pipe lines in 1994. Flotation technology was used for the cleaning of bottom sediments.157 tons of crude oil were removed during the course of 2-year experimental work from an area of 4,1 ha.The content of aliphatic and alicyclic oil hydrocarbons was reduced from 53,3 g/kg to 2,2 g/kg, on average.Hydrobiological investigations revealed that bottom sediments started to be inhabited by benthos organisms, dominantly Oligochaeta. Besides Oligochaeta, Chironomidae maggots and Bivalvia were detected. Theappearance of Macrozoobenthos organisms can serve as a bioindicator of water quality.